Eye movements and attention in visual feature search with graded target-distractor-similarity - Carolin Wienrich; Uta Heße; Gisela Müller-Plath (Bern Open Publishing, 2009)
We conducted a visual feature search experiment in which we varied the target-distractor-similarity in four steps, the number of items (4, 6, and 8), and the presence of the target. In addition to classical search parameters like error rate and reaction time (RT), we analyzed saccade amplitudes, fixation durations, and the portion of reinspections (recurred fixation on an item with at least one different item fixated in between) and refixations (recurred fixation on an item without a different item fixated in between) per trial. When target-distractor-similarity was increased, more errors and longer RTs were observed, accompa-nied by shorter saccade amplitudes, longer fixation durations, and more reinspec-tions/refixations. An increasing set size resulted in longer saccade amplitudes and shorter fixation durations. Finally, in target absent trials we observed more reinspections than refixations, whereas in target present trials refixations were more frequent than reinspec-tions. The results on saccade amplitude and fixation duration support saliency-based search theo-ries that assume an attentional focus variable in size according to task demands and a vari-able attentional dwell time. Reinspections and refixations seem to be rather a sign of in-complete perceptual processing of items than being due to memory failure.